L-theanine in the adjunctive treatment of generalized anxiety disorder: A double-blind, randomised, placebo-controlled trial. (March 2019) - Sarris, Jerome; Byrne, Gerard J.; Cribb, Lachlan; Oliver, Georgina; Murphy, Jenifer; Macdonald, Patricia; Nazareth, Sonia; Karamacoska, Diana; Galea, Samantha; Short, Anika; Ee, Carolyn; Birling, Yoann; et al.
Abstract: Partial or non-response to antidepressants in Generalized Anxiety Disorder (GAD) is common in clinical settings, and adjunctive biological interventions may be required. Adjunctive herbal and nutraceutical treatments are a novel and promising treatment option. L-theanine is a non-protein amino acid derived most-commonly from tea (Camellia sinensis) leaves, which may be beneficial in the treatment of anxiety and sleep disturbance as suggested by preliminary evidence. We conducted a 10-week study (consisting of an 8-week double-blind placebo-controlled period, and 1-week pre-study and 2-week post-study single-blinded observational periods) involving 46 participants with a DSM-5 diagnosis of GAD. Participants received adjunctive L-theanine (450–900 mg) or matching placebo with their current stable antidepressant treatment, and were assessed on anxiety, sleep quality, and cognition outcomes. Results revealed that adjunctive L-theanine did not outperform placebo for anxiety reduction on the HAMA (p = 0.73) nor insomnia severity on the Insomnia Severity Index (ISI; p = 0.35). However, LT treated participants reported greater self-reported sleep satisfaction than placebo (ISI item 4; p  = 0.015). Further, a separation in favour of L-theanine was noted on the ISI in those with non-clinical levels of insomnia symptoms (ISI ≤ 14; p = 0.007). No significant cognitive effects (trail making time and the modified emotional Stroop) were revealed. While this preliminary study did not support the efficacy of L-theanine in the treatment of anxiety symptoms in GAD, further studies to explore the application of L-theanine in sleep disturbance are warranted.